\[ \begin{array}{l} \text { (10) } x^{2}-4 x y-x+4 y=0 \\ x+2 y-3=0 \end{array} \]
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
Let’s solve the system of equations given: 1. The first equation is \(x^{2} - 4xy - x + 4y = 0\). 2. The second equation is \(x + 2y - 3 = 0\), which can be rearranged to express \(x\) in terms of \(y\): \[ x = 3 - 2y \] Now, substitute this expression for \(x\) into the first equation: \[ (3 - 2y)^{2} - 4(3 - 2y)y - (3 - 2y) + 4y = 0 \] Expanding \( (3 - 2y)^{2} \): \[ (3 - 2y)^{2} = 9 - 12y + 4y^{2} \] And substituting into the equation: \[ 9 - 12y + 4y^{2} - 4(3y - 2y^{2}) - (3 - 2y) + 4y = 0 \] Now simplify: \[ 9 - 12y + 4y^{2} - (12y - 8y^{2}) - 3 + 2y + 4y = 0 \] Combine like terms: \[ 9 - 3 + 4y^{2} + 8y^{2} - 12y + 2y + 4y = 0 \] \[ 6 + 12y^{2} - 6y = 0 \] Now set the equation to 0: \[ 12y^{2} - 6y + 6 = 0 \] Divide through by 6 to simplify: \[ 2y^{2} - y + 1 = 0 \] Now we can use the quadratic formula \(y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\): Here, \(a = 2\), \(b = -1\), and \(c = 1\): \[ b^2 - 4ac = (-1)^{2} - 4 \cdot 2 \cdot 1 = 1 - 8 = -7 \] Since the discriminant is negative, it means that there are no real solutions for \(y\). Therefore, there will also be no real solutions for \(x\). So the system has no real solutions! 🎉